1987
DOI: 10.1128/iai.55.9.2274-2280.1987
|View full text |Cite
|
Sign up to set email alerts
|

Marker exchange mutagenesis of the aerolysin determinant in Aeromonas hydrophila demonstrates the role of aerolysin in A. hydrophila-associated systemic infections

Abstract: We report here on the isolation of isogenic strains of Aeromonas hydrophila AB3 deleted for a segment of the aerolysin gene. All aer mutants obtained lacked the 49-kilodalton aerolysin gene product and were neither hemolytic for blood erythrocytes nor cytotoxic for Chinese hamster ovary tissue culture cells. One such mutant, AB3-5, was used in a mouse toxicity model to evaluate the role of aerolysin in the pathogenesis of A. hydrophila infections. The strain had a 50% lethal dose (LD50) of greater than 109 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(44 citation statements)
references
References 22 publications
3
41
0
Order By: Relevance
“…Aerolysin/hemolysin is commonly found in A. hydrophila strains that cause bacteremia [26]. Additionally, it has been observed that deletion mutants for the aerA gene (encoding aerolysin) are less virulent than parental strains [27]. Our study demonstrated that the occurrence of the aerolysin/hemolysin genes in A. popo¤i (92%) is similar to that in common clinical species (e.g.…”
Section: Resultssupporting
confidence: 58%
“…Aerolysin/hemolysin is commonly found in A. hydrophila strains that cause bacteremia [26]. Additionally, it has been observed that deletion mutants for the aerA gene (encoding aerolysin) are less virulent than parental strains [27]. Our study demonstrated that the occurrence of the aerolysin/hemolysin genes in A. popo¤i (92%) is similar to that in common clinical species (e.g.…”
Section: Resultssupporting
confidence: 58%
“…This toxin binds to a specific glycoprotein receptor on the surface of eukaryotic cells, inserts into the lipid bilayer and aggregates to form holes, leading to the destruction of the membrane and to osmotic lysis (Howard and Buckley, 1982;Parker et al, 1994;Nelson et al, 1997). In a mouse toxicity model, an aerolysindeficient A. hydrophila mutant was less virulent than wild-type A. hydrophila (Chakraborty et al, 1987;Wong et al, 1998). An in vitro study demonstrated that aerolysin impairs epithelial integrity by promoting TJ protein redistribution (Buecker et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The virulence of A. hydrophila is associated with the secretion of several extracellular proteins including aerolysin (Chakraborty et al, 1987), enterotoxin (Chakraborty et al, 1984), and protease (Leung and Stevenson, 1988). These extracellular proteins are secreted by a two-step pathway with the first step requiring the presence of a typical signal peptide so the extracellular protein can be translocated across the cytoplasmic membrane in a Sec-dependent manner (Wickner et al, 1991;Pugsley, 1993).…”
Section: Introductionmentioning
confidence: 99%